A systematic numerical study of the laminar burning velocity of iso-octane/syngas/air mixtures. (23rd February 2019) - Xu, Huanhuan; Liu, Fengshan; Sun, Shaozeng; Meng, Shun; Zhao, Yijun
Highlights: SL 0 of iso-octane/syngas/air mixtures were studied for three syngas compositions. Relationship between SL 0 and syngas addition was characterized by three parameters. H radical is found a kinetics indicator for SL 0 of iso-octane/syngas/air mixtures. SL 0 of iso-octane/syngas/air mixtures is controlled by small-hydrocarbons reactions. Abstract: The laminar burning velocities of iso-octane/syngas/air mixtures were numerically investigated using a detailed reaction mechanism over a wide range of equivalence ratio (0.4–1.4) at atmospheric and elevated pressure at an initial temperature of 423 K. The mole fraction of syngas in the fuel mixture was varied from the entire range of 0 (pure iso-octane) to 1 (pure syngas). To take into account the large variations of syngas compositions, the following three syngas compositions are considered: 75%H2 -25%CO, 50%H2 -50%CO, and 25%H2 -75%CO by volume. The results show that the laminar burning velocity of iso-octane/syngas/air mixtures increases with the content of syngas, especially for higher H2 content in syngas and rich mixtures. The enhanced burning velocity is attributed to the chemical effects of H2 in syngas. The burning velocity correlates linearly with the level of syngas dilution of the fuel mixture, regardless of how the syngas dilution ratio is defined when the dilution level is low. The linear correlation remains over a wide range of syngas dilution when the dilution ration is defined as that introduced by Yu et al. (1986). H2 addition and CO addition affect the radical pool differently and H is found to be a kinetics indicator for the burning velocity of iso-octane/syngas/air mixtures under the current conditions. Detailed sensitivity and pathway analysis was also conducted to identify reactions that significantly affect the burning velocity of iso-octane/syngas/air mixtures and to illustrate the kinetics interactions between H2, CO, and iso-octane in iso-octane/syngas/air mixtures.